Portraits and Poses : Female Intellectual Authority, Agency and Authorship in Early Modern Europe - Vanacker, Beatrijs; Deinsen, Lieke van (Book collections on Project MUSE., 2022)
The complex relation between gender and the representation of intellectual authority has deep roots in European history. 'Portraits and Poses' adopts a historical approach to shed new light on this topical subject. It addresses various modes and strategies by which learned women (authors, scientists, jurists, midwifes, painters, and others) sought to negotiate and legitimise their authority at the dawn of modern science in Early Modern and Enlightenment Europe (1600-1800). This volume explores the transnational dimensions of intellectual networks in France, Italy, Britain, the German states and the Low Countries. Drawing on a wide range of case studies from different spheres of professionalisation, it examines both individual and collective constructions of female intellectual authority through word and image. In its innovative combination of an interdisciplinary and transnational approach, this volume contributes to the growing literature on women and intellectual authority in the Early Modern Era and outlines contours for future research.